Fatter attraction: anthropometric and socioeconomic characteristics in the marriage market - Pierre-André Chiappori; Sonia Oreffice; Climent Quintana-Domeque (Institute for the Study of Labor (IZA), 2009)
We construct a matching model on the marriage market along more than one characteristic, where individuals have preferences over physical attractiveness (proxied by anthropometric characteristics) and market and household productivity of potential mates (proxied by socioeconomic characteristics), with a certain degree of substitutability between them. Men and women assess each other through an index combining these various attributes, so the matching is one-dimensional. We estimate the trade-offs among these characteristics using data from the PSID and the ECHP, finding evidence of compensation between anthropometric and socioeconomic characteristics. An additional unit of husband's (wife's) BMI can be compensated by a 0.3%-increase (0.15%-increase) in husband's (wife's) average (predicted) wage. Interestingly, these findings suggest that female physical attractiveness plays a larger role in men's assessment of a woman than male physical attractiveness does for women
Keywords: D1; J1; 330; BMI; height; wages; earnings; marriage market; Ehe; Matching; Gesundheitsrisiko; Anthropologie; Einkommen; Schätzung; EU-Staaten